New screening tool for neonatal nutritional risk in China: a validation study - Yan Hu; Mei Zhou; Yuwei Li; Huaying Yin; Xianhong Zhang (BMJ Open)
Objective A neonatal nutritional risk screening tool (NNRST) was developed by using Delphi and analytic hierarchy processes in China. We verified the accuracy of this tool and analysed whether it effectively screened neonates with nutritional risk.Design Prospective validation study.Setting and participants In total, 338 neonates who were admitted to the neonatal unit of Children’s Hospital of Chongqing Medical University from May–July 2016 completed the study. Nutritional risk screening and length and head circumference measurements were performed weekly. Weight was measured every morning, and other relevant clinical data were recorded during hospitalisation.Main outcome measures We evaluated the sensitivity, specificity, validity, reliability, and positive and negative predictive value of the screening tool. Various characteristics of neonates in different risk groups were analysed to determine the rationality of the nutritional risk classification.Results The sensitivity, specificity, and positive and negative predictive values were 85.11%, 91.07%, 60.61% and 97.43%, respectively. The criterion validity was texted by the Spearman correlation analysis (r=0.530) and independent samples non-parametric tests (p=0.000). The content validity (Spearman correlation coefficient) was 0.321–0.735. The inter-rater reliability (kappa value) was 0.890. Among the neonatal clinical indicators, gestational age, birth weight, length, admission head circumference, admission albumin, admission total proteins, discharge weight, discharge length and head circumference decreased with increasing nutrition risk level; the length of stay and the rate of parenteral nutrition support increased with increasing nutrition risk level. In the comparison of complications during hospitalisation, the incidence of necrotising enterocolitis and congenital gastrointestinal malformation increased with increasing nutrition risk level.Conclusion The validation results for the NNRST are reliable. The tool can be used to preliminarily determine the degree of neonatal nutritional risk, but its predictive value needs to be determined in future large-sample studies.Trial registration number ChiCTR2000033743.